(untitled) (مجلة العلوم الشاملة, 2026)
Environmental pollution is considered as one of the important and serious problem faces the humanity nowadays. Pollution can take the form of chemical substances or energy, such as noise, heat, or light. Pollutants are chemicals or materials that pollute the air, the water, or the soil in some form and are caused by human activities. Tree bark has been proven to be a valuable source of information on air pollution. bark has a large absorbent surface. Tree bark enables the identification and mapping of organic and inorganic air pollutants, Heavy metals are one of the important types of contaminants that can be found in the tree barks, which bark polluted with heavy metals have become common across the globe due to increase in geologic and anthropogenic activities. The Eucalyptus tree is an effective bio-indicator for heavy metals accumulation from road traffic. The aim of this study was to investigate and assess heavy metal pollution in the atmosphere such as zinc (Zn), cupper (Cu), cobalt (Co), cadmium (Cd), lead (Pb), nickel (Ni), and chromium (Cr) concentrated in the atmosphere of Tripoli city using Eucalyptus tree barks as a good indicator adsorbents of airborne pollutants. the samples were collected from 5 different localities in Tripoli city – Libya districts, which are having different traffic activities and all sites that have civil war, were takin in April 2024 and analyzed accomplished by flame atomic absorption spectroscopy technique (f - AAS). In this study, the result from heavy metal determination showed the presence of all the seven targeted elements in the barks samples. Highest mean concentrations of lead (40.770±1.43mg/kg), while Cd gave the lowest concentration at (0.065±0.003 mg/kg).